Factors Influencing Customers’ Bank Selection Decision in Nepal - Sahadev Bhatt, Dr. Swati Jain (International Journal of Advanced Science and Technology, 2020)
The research attempts to study the bank selection criteria of the Nepalese customers. The research is done through distributing and collecting 137 questionnaires to participants/respondents from the defined population of the clients of commercial bank in Bhairahawa city, Nepal. Respondent's views were presented and examined with test of reliability, descriptive statistics and Exploratory Factor Analysis (EFA). A finding from the study reveals that reliability is the most important criteria/factor influencing the customer in choosing a bank. The factor analysis results revealed that reliability and convenience are the most important determinants of bank choice. In contrast, value added services and responsiveness were the two least significant attributes of bank selection for Nepalese customers.